Les baladeurs MP3 en classe d'anglais de la 2nde au BTS – Représentations et attitudes des apprenants - Adeline Saverna (ALSIC: Apprentissage des Langues et Systèmes d'Information et de Communication)
This study looks into the impact of mobile digital tools on language learning, and in particular the impact of MP3 players in English classes. It consists in an exploratory study of 171 learners' beliefs and attitudes as regards the introduction and use of MP3 players in English classes in a high school. The investigation was based on a systemic approach of the learning context. In order to explore the learners' attitude, questionnaires were used. The results highlighted the absence of consensus in the acceptation of the MP3 player in English classes. A frequent use of the MP3 player in their daily lives does not lead to its appropriation in a school context. The MP3 player is not a real object – it is an artefact that is reconstructed according to the uses. Our study also showed that the learners' beliefs of the technological object depended on their beliefs of the other elements belonging to the learning context.